Pengaruh Praktikum Kimia SMA Skala Kecil Berbasis Inkuiri Terbimbing Terhadap Hasil Belajar Siswa - Utami, Putri Meinika (STKIP AGAMA HINDU SINGARAJA, 2024)
Small-Scale Chemistry Practicum Method Based on Guided Inquiry in improving the Learning Outcomes of Class XII Students at SMA Negeri 4 Singaraja and the Conventional Chemistry Practicum Method. This research is a Quasi Experimental research carried out on three main materials and two classes. In this research, there was an experimental class that was treated with the Small Scale Chemistry Practicum Method based on Guided Inquiry, a control class with the Conventional Chemical Practicum Method. Data collection uses observation sheets and tests. The research data were analyzed using the Wilcoxon Test.The results of the research show that learning using the Small-Scale Chemistry Practicum Method Based on Guided Inquiry improves student learning outcomes compared to the Conventional Chemistry Practicum Method. A significant difference was shown from the Wilcoxon results for Student Learning Outcomes with a value of Zcount > Ztabel (-7,789 ≤ 0.05). Apart from that, the average difference between posttest and pretest scores in the experimental class was 27% higher compared to the average posttest and pretest scores in the control class 11%.